Anticorruption policy in modern China: Basic principles and directions - Mamychev, Aleksey Yu. (2018)
The proposed study includes systematization and analysis of the theoretical and conceptual interpretations of "corruption" and "corruption interaction", discussion of the reasons and conditions for the development of corruption interaction in China, as well as consideration of the official assessments of anti-corruption activity and the main directions of prevention and combating corruption in Chinese society by Chinese scientists. Within the framework of this article, we analyze mainly current official positions, analytical materials, theoretical and conceptual versions and research approaches, in which the modern forms and practices of corruption interaction in China are being problematized. The work mainly uses Chinese sources and empirical data, which have been obtained by the authors during interviews (mainly an expert survey). The authors argue that both the scientific community, political analysts and public figures, as well as official representatives of the party, demonstrate unity in understanding the key characteristics of corruption and the main priorities of anti-corruption policy. At the same time, the very corruption phenomenon is treated as a socially negative phenomenon of the modern life of Chinese society, which is of complex nature.